Electronically Tunable Current-mode High-order Ladder Low-pass Filters Based on CMOS Technology - T. Kunto; P. Prommee; M. T. Abuelma'atti (My University, 2015)
This paper describes the design of current mode low-pass ladder filters based on CMOS technology.The filters are derived from passive RLC ladder filter prototypes using new CMOS lossy and lossless integrators.The all-pole and Elliptic approximations are used in the proposed low-pass filter realizations.The proposed two types of filter can be electronically tuned between 10 kHz and 100 MHz through bias current from 0.03 µA to 300 µA.The proposed filters use 1.5 V power supply with 3 mW power consumption at 300 µA bias current.The proposed filters are resistorless, use grounded capacitors and are suitable for further integration.The total harmonic distortion (THD) of the low-pass filters is less than 1% over the operating frequency range.PSPICE simulation results, obtained by using TSMC 0.18µm technology, confirm the presented theory.
Keywords: Harmonic; Voltage-controlled filter; Electronic filter topology; Analog and Mixed-Signal Circuit Design